Perubahan ekologi pantai paciran-brondong di lamongan tahun 1930-2010 - Ahmad Sholehuddin Suryanullah; Dewa Agung Gede Agung; Ronal Ridhoi (Historiography: Journal of Indonesian History and Education, 2021)
Ecological changes on the coast of Lamongan Beach are an interesting discussion to discuss. Since 1930,  the coast of Lamongan Beach has played an important role in the transportation of spices from the interior to the port. The study is focused on the processes and factors that cause changes in the coastal ecology of Lamongan Beach. This study uses the historical method by reading in depth in the form of archives, newspapers, articles, books, and maps. This study shows that ecological changes can be carried out by human activities and natural activities, the existence of this connection which causes a change of function, from rice fields to settlements, tourist attractions, ports, this which causes ecological changes in 1930-2010 on the coast of Lamongan Beach.Perubahan ekologi di pesisir Pantai Lamongan menjadi pembahasan yang menarik untuk dibahas. Sejak tahun 1930, pesisir Pantai Lamongan sudah berperan penting dalam jalur pengangkutan rempah-rempah dari pedalaman ke pelabuhan. Studi ini memfokuskan pada proses serta faktor yang menyebabkan perubahan ekologi pesisir Pantai Lamongan. Penelitian ini menggunakan metode sejarah dengan melakukan pembacaan secara mendalam sumber-sumber berupa arsip, berita koran, artikel, buku, dan peta. Studi ini menunjukkan bahwa perubahan ekologi bisa dipengaruhi oleh aktifitas manusi dan aktifitas alam, adanya keterkaitan itu yang menyebabkan alih fungsi lahan, dari persawahan menjadi pemukiman, tempat wisata, pelabuhan, hal itu yang menyebabkan perubahan ekologi pada tahun 1930-2010 di pesisir Pantai Lamongan.